2019
DOI: 10.3390/nu11102309
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Spirulina platensis Extract against Dextran-Sulfate-Sodium-Induced Ulcerative Colitis in Rats

Abstract: Inflammatory bowel disease is a multifactorial inflammatory condition. This study aimed to test the protective effects of Spirulina platensis against ulcerative colitis (UC). UC was induced in thirty-six male Wistar rats by adding dextran sulfate sodium (DSS) to their drinking water, while a control group received only drinking water. UC rats were equally-divided into six groups that received a single oral daily dose of vehicle (DSS), sulfasalazine (SSZ, 50 mg/kg/day), chloroform or the hydroalcoholic extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 77 publications
(122 reference statements)
0
18
0
Order By: Relevance
“…The groups comprised low-fat diet-fed rats (LFD, 10 kcal% fat D12450B, control group), HFD-fed rats (45 kcal% fat D12451, FBSH Biopharmaceutical Co., Ltd) and rats fed an HFD with 3% Spirulina platensis (SP group). 23,24 100% pure S platensis powder was obtained from Lianmai Biotech Ltd. and administered it 3 g/100 g of diet to the experimental animals. We closely recorded each rat's bodyweight and food intake on a weekly basis.…”
Section: Animal Samples Experimental Design and Sample Collectionmentioning
confidence: 99%
“…The groups comprised low-fat diet-fed rats (LFD, 10 kcal% fat D12450B, control group), HFD-fed rats (45 kcal% fat D12451, FBSH Biopharmaceutical Co., Ltd) and rats fed an HFD with 3% Spirulina platensis (SP group). 23,24 100% pure S platensis powder was obtained from Lianmai Biotech Ltd. and administered it 3 g/100 g of diet to the experimental animals. We closely recorded each rat's bodyweight and food intake on a weekly basis.…”
Section: Animal Samples Experimental Design and Sample Collectionmentioning
confidence: 99%
“…As far as we know, this study is the first systematic review and meta‐analysis of clinical trials determining the effects of spirulina administration on concentrations of inflammatory cytokines including IL‐2, IL‐6 and TNF‐α, as well as oxidative stress indicators including MDA and TBARS levels. Spirulina, a microalga that is used to produce nutritional supplements nowadays, possesses different kinds of clinical and physiological implications that are profitable for improving various inflammatory and oxidative stress‐related disorders including cancers, arthritis, dementia, diabetes, vascular disease, atherosclerosis, asthma and inflammatory bowel disease 32–38 . For instance, recent evidence suggested that spirulina supplementation improved immune function after chemotherapy in patients with malignant tumours by supporting the maintenance of white blood cell, neutrophils, immunoglobulin M and CD8 + T cell population levels 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, long‐term supplementation of spirulina resulted in an improvement of bronchial asthma by combating detrimental damage and inflammation in the respiratory cell lining 37 . Moreover, hydroalcoholic extract of spirulina was found to be an effective treatment of ulcerative colitis by modulating local and systemic inflammation 38 …”
Section: Discussionmentioning
confidence: 99%
“…More recently, the beneficial effects of SPI in dextran sulfate sodium (DSS)-induced colitis have been examined in rats. 15 The effects of SPI extracts have never been explored in DSS-induced intestinal inflammation in mice. The DSS model is one of the most used approaches to study inflammatory bowel disease (IBD) and is believed to resemble the features of flares in UC 13 and CD (mainly transmural inflammation).…”
Section: Introductionmentioning
confidence: 99%